Analisis konten budaya kolaboratif berbasis Grounded Theory menggunakan Text Mining - Julians, Adhe Ronny; Manongga, Daniel Herman Fredy; Hendry, Hendry (AITI, 2024)
Creating a collaborative culture of innovation in an organization is very important today. A collaborative culture of innovation is not just about physically working together but also about creating an environment that supports open communication, appreciation for new ideas, and acceptance of risk. Organizations that embrace this culture can create significant added value and thrive in an ever-changing environment. This research aims to conduct a content analysis of several Grounded Theory-based reputable scientific articles using Text Mining, which involves using coding techniques to classify information and identify certain categories or codes representing certain text elements. The analysis results are a conceptual network model that connects elements that influence collaborative culture on innovation, such as Openness, Diversity, Shared Goals, Trust, Teamwork, Support, and Use of Technology. Organizations use this model to create a collaborative culture of innovation in their environment, and it can be used in further research to test the model using statistical tests.